IMPROVING THE FUNCTIONING OF TERRITORIAL PUBLIC SELF-GOVERNMENT (USING THE EXAMPLE OF THE KHABAROVSK CITY URBAN DISTRICT) - Vitaly E. Morozov (Russian Studies in Law and Politics)
Based on the results of the analysis of individual stages of legislative consolidation of TPSG, in this article the author comes to the conclusion, firstly, that there are three such stages, which are related to the number of adopted legislative acts on local self-government, and, secondly, about the changes in regional legal regulation in this area. Due to the imperative norm of the lack of powers of the subjects of the Russian Federation for the legal regulation of the organization and functioning of TPSG, regions currently have the right at the legislative level to establish only forms of support for TPSG.